Penerapan Model Pembelajaran Bermain Peran untuk Meningkatkan Keterampilan Berbicara Siswa pada Mata Pelajaran Bahasa Indonesia di Kelas IV SD Negeri 101771 Tembung - Lubis, Dita Pradilla Melenia; Nurmairina, Nurmairina (Indonesian Research Journal on Education, 2022)
The low mastery of student learning on the competence of speaking skills in Indonesian class IV subjects at SD Negeri 101771 Tembung. This is evidenced from the results of observations and interviews of researchers in the pre-study with field teachers, where there are only 9 or 30% of 30 students who get scores above the KKM > 75 in the complete category. So that there are still many fourth grade students at SD Negeri 101771Tembung who have not completed or have not achieved scores above the KKM <75, there are 21 or 70% of the 30 students who get marks in the incomplete category. The purpose of this research is to improve students' speaking skills in Indonesian subjects by applying a role-playing learning model in class IV SD Negeri 101771 Tembung. The method used in this research is Classroom Action Research (CAR) which is carried out in two cycles and each cycle is carried out in two meetings. Each meeting is divided into 4 stages, namely planning, implementation, observation and reflection. The subjects of this study were class IV SD Negeri 101771 Tembung, totaling 30 people. Data collection techniques used in this study were observation sheets as instruments for teacher and student activities and an assessment rubric to calculate students'speaking skills and also documentation. The results of this study indicate that there is an increase in student learning outcomes from para-cycle activities, in the pre-cycle the percentage of completeness is 30% of the number of students and the first cycle has increased with the number of completeness 74% until the final cycle the increase is seen to be more significant with the percentage of student completeness is 93% . So itcan be concluded that the role playing learning model can improve students' speaking skills.